The Effect of Employer Branding and Electronic Word of Mouth (E-WOM) on Intention to Apply Mediated by Corporate Reputation with Social Media as a moderation Variable in E-Commerce Companies in Indonesia - Aghna, Muhammad Nabil; Kurniawan, Dediek Tri (Departemen Manajemen Fakultas Ekonomi dan Bisnis Universitas Negeri Malang, 2023)
Competition between companies is not only to win the market, but also in getting the best employees. Potential employees tend to be more selective in choosing which company to apply to. This study was conducted to see how the effect of the application of employer branding, and electronic word of mouth communication that occurs on the desire of potential employees to apply for jobs in e-commerce companies which are also seen as mediation and moderation relationships. Respondents of this study amounted to 398 consisting of FEB students from 3 universities that have a high level of employability in their graduates. The data analysis method used in this study is using the Structural Equation Model (SEM) with SMART-PLS software. In this study, it was found that there was a positive influence of the application of employer branding on the desire of potential employees to apply to e-commerce companies. So that the application of employer branding in e-commerce companies is important to attract potential applicants.